Outcome in noncritically ill patients with acute kidney injury requiring dialysis: Effects of differing medical staffs and organizations. Issue 30 (July 2016) - Fagugli, Riccardo Maria; Patera, Francesco; Battistoni, Sara; Tripepi, Giovanni
Abstract : Abstract: Acute kidney injury requiring dialysis (AKI-D) treatment has significantly increased in incidence over the years, with more than 400 new cases per million population/y, 2/3 of which concern noncritically ill patients. In these patients, there are little data on mortality or on information of care organization and its impact on outcome. Specialty training and integrated teams, as well as a high volume of activity, seem to be linked to better hospital outcome. The study investigates mortality of patients admitted to and in-care of nephrology (NEPHROpts), a closed-staff organization, and to other medical wards (MEDpts), representing a model of open-staff organization. This is a single center, case–control cohort study derived from a prospective epidemiology investigation on patients with AKI-D admitted to or in-care of the Hospital of Perugia during the period 2007 to 2014. Noncritically ill AKI-D patients were analyzed: inclusion and exclusion criteria were defined to avoid possible bias on the cause of hospital admittance and comorbidities, and a propensity score (PS) matching was performed. Six hundred fifty-four noncritically ill patients were observed and 296 fulfilled inclusion/exclusion criteria. PS matching resulted in 2 groups: 100 NEPHROpts and 100 MEDpts. Characteristics, comorbidities, acute kidney injury causes, risk–injury–failure acute kidney injury criteria, and simplified acute physiology score (SAPS 2) were similar. Mortality was 36%, and a difference was reported between NEPHROpts and MEDpts (20% vs 52%, χ 2 = 23.2, P < 0.001). Patients who died differed in age, serum creatinine, blood urea nitrogen/s.Creatinine ratio, dialysis urea reduction rate (URR), SAPS 2 and Charlson score; they presented a higher rate of heart disease, and a larger proportion required noradrenaline/dopamine for shock. After correction for mortality risk factors, multivariate Cox analysis revealed that site of treatment (medical vs nephrology wards) represents an independent risk factor of mortality (relative risk = 2.13, 95% confidence interval = 1.25, 3.63; P < 0.01). Other independent risk factors were age, URR, s.Creatinine at hemodialysis beginning, and SAPS 2 score. In our context, we have documented that noncritically ill AKI-D patients, who represented 2/3 of the population, had high in-hospital mortality (36%), and that a closed-staff specialty medical organization, such as a Nephrology team, seems to guarantee a better outcome than general medical organizations. The significance in healthcare system organization and resource allocation could be important.